Learning Writing Short Story Through Wayang Beber Media for 9th Grade Students of SMP N 4 Ponorogo - Wuryantoro, Aris; *, Misriyati (Proceeding of International Conference on Teacher Training and Education, 2016)
This research aims to obtain a description of the planning, implementation, and evaluation of the learningwriting short story through Wayang Beber media for 9th grade students of SMP N 4 Ponorogo, East Java. Thisresearch was carried out for 4 months in the 9th students of SMP N 4 Ponorogo Academic Year 2014/2015.This research uses qualitative research design by using interviewing and observation techniques to collect thedata. The research reveals: (1) the planning of learning writing short story through wayang beber can beaccepted and implemented by the students. The students are happy and comfortable in learning writing shortstory; (2) the implementation of learning writing short story through wayang beber run well, smooth, relaxed;and (3) the evaluation of learning writing short story through wayang beber writing learning of short storiesthrough the medium of combined musical Javanese wayang beber is very effective because wayang beber issomething new and inspiring for students to finish their asigments.